Produção de ácido indol acético in vitro por Torulaspora globosa - Albertini, Jéssica (Universidade Federal de São Carlos, 2017)
The indole acetic acid (IAA) is a phytohormone capable of providing fast responses to plant development such as cell elongation and differentiation and division of cells. It is known that exist in the rhizosphere there are yeasts capable of assisting the plant development by the IAA production. In this study, the objective was isolate yeasts of the rhizosphere and select lineages capable of producing IAA; the selected lineage was evaluated for the influence of temperature, pH, agitation, carbon and nitrogen on the production of IAA. For isolation, corn rhizosphere and sugarcane were sampled from the campus area of UFSCar, Araras/SP. The samples were plated on YEPD medium, Sabouraud and BDA. The lineages were selected using colorimetric methodology, with Salkowsky reagent. The best results were evaluated for the influence of factors in the production of AIA, through experimental planning with multivariate analysis. Six yeast strains were isolated; the strain 6S01, identified as Torulaspora globosa, was selected. The results of the multivariate analysis show that among the studied factors, which significantly affected the production of IAA were pH, agitation and nitrogen. The pH showed the greatest influence on production, because it affected significantly at all times evaluated; the highest recorded production values were obtained in the treatment in which the initial pH of the medium was adjusted to 9,0. The highest yields occurred between 24 and 48 hours of incubation, and the maximum production was 217,73 μg/mL. It was observed that, in the tests in which there was no addition of nitrogen source in the culture medium, the production was higher; probably tryptophan provided as a precursor molecule of AIA synthesis was used by tthe yeast as a nitrogen source and was better absorbed in the absence of other sources of the nutrient. It is concluded that the yeast T. globosa (6S01), isolated from maize rhizosphere presents capacity of high production of IAA, with potential for large scale production; the best conditions for the production are in the absence of nitrogen source and in alkaline medium.
Keywords: Torulaspora globosa; Análise multivariada; Nitrogênio; Triptofano; Multivariate analysis; Nitrogen; Tryptophan; CIENCIAS BIOLOGICAS